2017
DOI: 10.1039/c7sc00201g
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular anion recognition in water: synthesis of hydrogen-bonded supramolecular frameworks

Abstract: Charge-assisted hydrogen bonds between a tetratopic receptor and terephthalate anions assemble a switchable supramolecular framework material in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
132
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 71 publications
4
132
0
Order By: Relevance
“…[12] Building upon this result,w eh ypothesized that as imilars tructure could be prepared using the extended tecton TBA 2 ·biphenyldicarboxylate. [12] Building upon this result,w eh ypothesized that as imilars tructure could be prepared using the extended tecton TBA 2 ·biphenyldicarboxylate.…”
Section: Framework Series A(tetraamidinium 1 4 + + and Dicarboxylates)mentioning
confidence: 97%
See 2 more Smart Citations
“…[12] Building upon this result,w eh ypothesized that as imilars tructure could be prepared using the extended tecton TBA 2 ·biphenyldicarboxylate. [12] Building upon this result,w eh ypothesized that as imilars tructure could be prepared using the extended tecton TBA 2 ·biphenyldicarboxylate.…”
Section: Framework Series A(tetraamidinium 1 4 + + and Dicarboxylates)mentioning
confidence: 97%
“…[12] pared from two tetravalent tectons, ast hese may be even more robust. [12] pared from two tetravalent tectons, ast hese may be even more robust.…”
Section: Framework Series C( Tetraamidinium and Tetracarboxylates)mentioning
confidence: 99%
See 1 more Smart Citation
“… Examples of self‐assembled structures prepared using charge‐assisted hydrogen bonds: a) Wais Hosseini's synthesis of 1D supramolecular polymers, b) general representation of Ward's synthesis of a family of guanidinium–sulfonate frameworks, and c) White's synthesis of amidinium–carboxylate frameworks …”
Section: Introductionmentioning
confidence: 99%
“…Ward's group has pioneered the assembly of simple guanidinium cations with polysulfonate molecules to give ready access to a large family of guanidinium–sulfonate frameworks (Figure b), many of which encapsulate organic guest molecules . Inspired by these studies, we recently reported the synthesis of supramolecular organic frameworks in water based on the favorable interactions between a tetraamidinium cation and terephthalate anions (Figure c) …”
Section: Introductionmentioning
confidence: 99%